Mixed-type literature review of research on L2 learning in and through the linguistic landscape - Wiśniewska, Danuta (Neofilolog, 2024)
The aim of this paper is to provide a review of articles reporting on research related to the linguistic landscape as applied to foreign language education, with a focus on the conceptualisation of the linguistic landscape, main themes, and research methods and distribution across years, languages taught and countries of research. The search for relevant articles published between 2003–2023 was conducted in databases: Web of Science, ERIC, MLA, and Scopus. The search yielded a total sample of 20 articles. The presentation of the main results of the review is followed by suggestions of topics for further research and reviews of a broader scope.